2015
DOI: 10.1038/srep14196
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Spin Hall States in Stanene/Ge(111)

Abstract: For topological insulators to be implemented in practical applications, it is a prerequisite to select suitable substrates that are required to leave insulators’ nontrivial properties and sizable opened band gaps (due to spin-orbital couplings) unaltered. Using ab initio calculations, we predict that Ge(111) surface qualified as a candidate to support stanene sheets, because the band structure of √3 × √3 stanene/Ge(111) (2 × 2) surface displays a typical Dirac cone at Γ point in the vicinity of the Fermi level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 37 publications
(40 reference statements)
1
19
0
2
Order By: Relevance
“…Ethynyl derivative-functionalized stanene (SnC 2 X: X ¼ H, F, Br, and I) has been studied by Zhang et al 15 Recently, it was found that the strong interaction with the substrate can disturb the Dirac cones. 16 The H-BN 17 and Ge (1 1 1) substrates 18 will induce a band gap in stanene, transforming it into a quantum spin Hall phase.…”
Section: Introductionmentioning
confidence: 99%
“…Ethynyl derivative-functionalized stanene (SnC 2 X: X ¼ H, F, Br, and I) has been studied by Zhang et al 15 Recently, it was found that the strong interaction with the substrate can disturb the Dirac cones. 16 The H-BN 17 and Ge (1 1 1) substrates 18 will induce a band gap in stanene, transforming it into a quantum spin Hall phase.…”
Section: Introductionmentioning
confidence: 99%
“…First principle calculations suggest that a silver (1 1 1) surface could be also an ideal candidate for growing large-area, high-quality monolayer stanene [12]. Unique physical properties for stanene have been predicted, such as the QSH effect [13,14], topological superconductivity [15], giant magnetoresistance [16], perfect spin filter [16], and anomalous Seebeck effect [17]. All these properties are based on low-buckled stanene.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-like group-IV, such as silicene 1 – 3 , germanene 1 , 4 , 5 , and stanene 6 , 7 , with two-dimensional (2D) honeycomb geometry have attracted much attention in recent years due to their exotic properties 8 11 . Their low-buckled geometries with a mixing of and hybrids but the same lateral symmetry as graphene (Gr) are responsible for extraordinary electronic and optical properties 1 , 8 , e.g., the appearance of Dirac cones near the K corner points of the hexagonal Brillouin zone (BZ).…”
Section: Introductionmentioning
confidence: 99%